Research of Crawl Phenomenon of Chain Propulsion Equipment - Zhai Wang; Liu Jia; Qin Li (Jixie chuandong)
The causes of crawl phenomenon of chain propulsion equipment are analyzed. According to the structure characteristics of the equipment,the chain is regarded as an elastic element,also considering the polygon effect when the sprocket wheel rotates,the motion differential equations are set up. Based on the solving result,the impacts of chain stiffness,sprocket parameter on the velocity of the load is analyzed. Then,the stiffness weak of the chain is the main reason which leads to the load crawl,especially when the equipment starts or the resistance changes. The elastic characteristics of the chain will cause the load speed change regularly,and produce resonance with the sprockets easily. At last,several measures for solving crawling problems is proposed directing to a particular equipment.